Novel 3‐D cell culture system for in vitro evaluation of anticancer drugs under anchorage‐independent conditions. Issue 12 (19th December 2016) - Aihara, Ayako; Abe, Natsuki; Saruhashi, Koichiro; Kanaki, Tatsuro; Nishino, Taito
Abstract : Anticancer drug discovery efforts have used 2‐D cell‐based assay models, which fail to forecast in vivo efficacy and result in a lower success rate of clinical approval. Recent 3‐D cell culture models are expected to bridge the gap between 2‐D and in vivo models. However, 3‐D cell culture methods that are available for practical anticancer drug screening have not yet been fully attained. In this study, we screened several polymers for their ability to suspend cells or cell spheroids homogeneously in a liquid medium without changing the viscosity behavior, and identified gellan gum (FP001), as the most potent polymer. FP001 promoted cell dispersion in the medium and improved the proliferation of a wide range of cancer cell lines under low attachment conditions by inhibiting the formation of large‐sized spheroids. In addition, cancer cells cultured with FP001‐containing medium were more susceptible to inhibitors of epidermal growth factor (EGF) signaling than those cultured under attachment conditions. We also showed that ligands of the EGF receptor family clearly enhance proliferation of SKOV3 ovarian carcinoma cells under anchorage‐independent conditions with FP001. Consistent with this result, the cells grown with FP001 showed higher EGF receptor content compared with cells cultured under attachment conditions. In conclusion, we developed a novel 3‐D cell culture system that is available for high throughput screening of anticancer agents, and is suitable for evaluation of molecular‐targeted anticancer drugs. Three‐dimensional cell culture using FP001 will be of value in the development of useful technologies for anticancer drug discovery. Abstract : 3D cell culture using FP001 will be valuable for anticancer drug discovery.